Formulasi Minuman Kesehatan Ekstrak Jamur Tiram Putih (Pleurotus ostratus) Kaya β-Glukan - . Masitoh; Leni Ariyanti; Fitrah Hadi Firdaus; Ade Irma; Erni Apriliana; . Irzaman; Mersi Kurniati; Maya Risanti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Situ Ilir Village located in Cibungbulang Subdistrict, Bogor District, West Java, which has the potential for substantial human resources for the more advanced, unfortunately majority of people's livelihood as traditional farmers. One of the potential contained in this village is oyster mushroom farm. The results of guidance and cooperation of the students of physics IPB like oyster mushroom production training has been carried out in this village, however the marketing less than the maximum. For example many young mushroom or fungus inadvertently severed by farmers to be not worth selling and discarded. By looking at this potential, then came the idea to create a health drink of the oyster mushroom. The aim of this community service are able to give the value of the oyster mushroom selling agricultural products, to increase public knowledge about the benefits of oyster mushrooms, and maximize human resources at Situ Ilir Village. The method used in this training are extension of oyster mushrooms, manufacture of health drinks, and β-glucan analysis using Fourier Transform Infrared (FTIR). This activity resulted in products processed from oyster mushroom as a health drink rich in β-glucan shown from the results of FTIR analysis, that can increase the sale value of the oyster mushroom and enhance the creativity of the human resources in the Situ Ilir Village, Cibungbulang Subdistrict, Bogor District, West Java.